Flujometría doppler de arterias uterinas como predictor de macrosomia fetal - Limay-Ríos, Oscar Antonio (2016)
Objectives: To determine the relationship between the average pulsatility index of the uterine arteries taken by ultrasound inpregnant women between 11 and 14 and 20 to 26 weeks of gestation with neonatal macrosomia. Materials and methods:Prospective, longitudinal, analytical study. A total of 3,279 pregnant women attended at the National Maternal Perinatal Institutebetween 2011 and 2014, of whom 952 were patients between 11 and 14 weeks and 2327 between 20 and 26 weeks, two groupswere formed: 11 to 14 and 20 to 26 weeks; The weights considered for the comparison were: 3,600, 3,800, 4,000, 4,200 and 4,400grams, a correlation was performed by the Pearson method, statistical significance was performed by means of Chi square test forboth groups, to calculate the probability Of occurrence of events was calculated odss ratio and to evaluate the precision were usedconfidence intervals, subsequently constructed a ROC curve to precise sensitivity and false positive rate.